2012
DOI: 10.1017/s0008938912000040
|View full text |Cite
|
Sign up to set email alerts
|

Local Catholicism as Transnational War Experience: Everyday Religious Practice in Occupied Northern France, 1914–1918

Abstract: The Great War is not a historical episode that easily lends itself to studying the subtleties of religious belief systems. Believers on opposite sides claimed that they were engaged in a just war of defense against aggression. They argued that God was on their side, and they prayed for victory of their nation—even if that meant the destruction of their fellow believers who were now considered the enemy. Despite Catholic claims to internationalism and universalism, the overwhelming majority of Catholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As a priest serving in the French troops wrote: 'The love of our country and the love of God so long separated were now as one' (Gaëll 1916, p. 3). Other works in local history confirm the emergence of a proper 'patriotic Catholicism, which is also Catholic patriotism' (Becker 1998, p. 10;Houlian 2012).…”
Section: After World War I: Towards Popular/people's Partiesmentioning
confidence: 94%
“…As a priest serving in the French troops wrote: 'The love of our country and the love of God so long separated were now as one' (Gaëll 1916, p. 3). Other works in local history confirm the emergence of a proper 'patriotic Catholicism, which is also Catholic patriotism' (Becker 1998, p. 10;Houlian 2012).…”
Section: After World War I: Towards Popular/people's Partiesmentioning
confidence: 94%
“…These scholars also provide ample evidence that the shock of industrialized warfare drove just as many, if not more, Europeans to embrace traditional beliefs as it did to inspire the avant-gardism of others. 87 Emmerick's Weimar cult also reflected these nuances. Even as articles and speeches sought to create Emmerick anew as a twentieth-century German Führerin, her potency as a symbol derived from her existing veneration as a nineteenth-century Westphalian Mystikerin.…”
Section: Reimagination Of the Past And Presentmentioning
confidence: 99%
“…9 However, few works deal exclusively with religion in occupied France. Patrick J. Houlihan emphasised the way in which transnational Catholicism brought some French Catholics closer to Catholic Bavarian troops, 10 whereas Carine Cnudde-Lecointre demonstrated that here, as elsewhere, certain Catholics viewed the war as a divine punishment for the sins of secular France. 11 This was partly why some individuals described the occupation as an expiatory experience, a 'Calvary' and 'martyrdom' .…”
Section: Religious Conflictmentioning
confidence: 99%